Antidoti - Možina, Martin (Medicinski razgledi, 2009)
In addition to symptomatic and supportive treatment, decontamination of the digestive tract is frequently the only therapeutic measure in the case of poison ingestion. Decontamination of the skin and eyes can also be performed, and if corrosive substances are ingested, dilution may be attempted. Decontamination methods for the digestive tract include: induction of vomiting, gastric lavage, administration of activated charcoal, intestinal lavage, forced diarrhea as well as high enema, gastroscopy and gastrotomy. Generally, decontamination of the digestive tract is most effective during thefirst hour after poison ingestion. Elimination methods are used to promote the poison's excretion from the body following its absorption. Elimination of poisons is also accelerated by administering repeated doses of activated charcoal, forced diuresis, alkalinisation and acidification of urine and extracorporeal techniques (peritoneal dialysis, hemodialysis, hemoperfusion, hemofiltration, plasmapheresis) and exchange transfusion. The decision on the need for and method of decontamination or poison elimination should be based on prior assessment of the severity of poisoning and time of poisoning, as well as the assessment of the poison's dangerousness in cooperation with the Centre for Intoxications, and the possibility of safe performance of procedures. No method should be used routinely without taking into account itsindications, contraindications and possible complications.
Keywords: Atropin; Poisoning; Drug Therapy; Zastrupitev; Antidotes; Antidoti; Acetilcistein; Acetylcysteine; Amilnitrit; Atropine; Amyl Nitrite; Dimerkaprol; Biperiden; Edetska kislina; Dantrolene; Deferoksamin; Dantrolen; Edetic Acid; zastrupitve; Deferoxamine; Dimercaprol; zdravljenje; therapy; zdravila; drug